نحو خوصصة الاراضي الفلاحية العامة في الجزائر رؤية تقييمية لمشروع قانون بيع او تأجير الاراضي التابعة للأملاك الوطنية الخاصة - احمد قايد, نور الدين; عبة, فريد (مجلة الاقتصاديات المالية البنكية وإدارة الأعمال; No 01 (2012): مجلة الاقتصاديات المالية البنكية وإدارة, 2018)
There were many of legislation that dealt with organizing the relationship between the land and the farmer with respect to land of the property of their national, because it is located in the fertile regions of the country and this is what led to the complexity of the Status property, which led to the freezing of the market, and highlighted the phenomenon of stability and confidence among the beneficiaries, which is exacerbated by the trading Ocean, especially the financial of it. This situation that came to the Algerian agriculture has delegated to consider in the sale of agricultural land autoger of the property right to the use of an alternative national permanent